Glassy GaS: transparent and unusually rigid thin films for visible to mid-IR memory applications. Issue 44 (4th November 2020) - Tverjanovich, Andrey; Khomenko, Maxim; Bereznev, Sergei; Fontanari, Daniele; Sokolov, Anton; Usuki, Takeshi; Ohara, Koji; Le Coq, David; Masselin, Pascal; Bychkov, Eugene
Abstract : An unusually rigid glassy GaS film obtained by PLD shows an excellent light-induced damage threshold promising for memory applications. Abstract : Phase-change materials based on tellurides are widely used for optical storage (DVD and Blu-ray disks), non-volatile random access memories and for development of neuromorphic computing. Narrow-gap tellurides are intrinsically limited in the telecom spectral window, where materials having a wider gap are needed. Here we show that gallium sulfide GaS thin films prepared by pulsed laser deposition reveal good transparency from the visible to the mid-IR spectral range with optical gap E g = 2.34 eV, high refractive index n R = 2.50 over the 0.8 ≤ λ ≤ 2.5 μm range and, unlike canonical chalcogenide glasses, the absence of photo-structural transformations with a laser-induced peak power density damage threshold above 1.4 TW cm −2 at 780 nm. The origin of the excellent damage threshold under a high-power laser and UV light irradiation resides in the rigid tetrahedral structure of vitreous GaS studied by high-energy X-ray diffraction and Raman spectroscopy and supported by first-principles simulations. The average local coordination number appears to be 〈 m 〉 = 3.44, well above the optimal connectivity, 2.4 ≤ 〈 m 〉 ≤ 2.7, and the total volume of microscopic voids and cavities is 34.4%, that is, lower than for the vast majority of binary sulfide glasses. The glass–crystal phase transition in gallium sulfide thin films may be accompanied by a drastic change in the nonlinear optical properties, opening up a new dimension for memory applications in the visible to mid-IR spectral ranges.